2016
DOI: 10.3892/etm.2016.3413
|View full text |Cite
|
Sign up to set email alerts
|

HSP60 mediates the neuroprotective effects of curcumin by suppressing microglial activation

Abstract: Curcumin has anti-inflammatory and antioxidant properties and has been widely used to treat or prevent neurodegenerative diseases. However, the mechanisms underlying the neuroprotective effects of curcumin are not well known. In the present study, the effect of curcumin on lipopolysaccharide (LPS)-stimulated BV2 mouse microglia cells was investigated using enzyme-linked immunosorbent assays of the culture medium and western blotting of cell lysates. The results showed that curcumin significantly inhibited the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…71 In vitro, curcumin has previously been shown to reduce the expression of pro-inflammatory mediators and cytokines in activated microglial cells via different signaling pathways. 23,25,[72][73][74][75][76] Curcumin stimulation could also reduce reactivity/activation in astrocytes or astrocytic cell culture models upon different challenges. [77][78][79] In accordance with these findings, we could show that our liposomal curcumin formulation could inhibit LPS-induced cytokine expression by human microglial cells, often even more robust than free curcumin.…”
Section: Discussionmentioning
confidence: 99%
“…71 In vitro, curcumin has previously been shown to reduce the expression of pro-inflammatory mediators and cytokines in activated microglial cells via different signaling pathways. 23,25,[72][73][74][75][76] Curcumin stimulation could also reduce reactivity/activation in astrocytes or astrocytic cell culture models upon different challenges. [77][78][79] In accordance with these findings, we could show that our liposomal curcumin formulation could inhibit LPS-induced cytokine expression by human microglial cells, often even more robust than free curcumin.…”
Section: Discussionmentioning
confidence: 99%
“…Jobin et al showed that curcumin promoted the neuroprotectiove effect afflicted with ischemia by suppressing an inflammatory reaction modulated by the TLR4/p38/MAPK pathway [26]. Also, curcumin resulted in the blockade of lipopolysaccharide (LPS)-activated HSP60/TLR-4/MyD88/NF-κB pathway in BV2 microglia, exerting anti-inflammatory and neuroprotective effects [27]. Similarly, curcumin efficiently attenuated the production of pro-inflammatory mediators nitric oxide (NO) and prostaglandin E-2 (PGE-2), as well as the release of pro-inflammatory cytokines interleukin (IL)-1β, IL-6, and TNF-α in LPS-induced microglia [28].…”
Section: Discussionmentioning
confidence: 99%
“…In mice liver cells with T-cell lymphoma, the expression of GST, GR, and NAD(P)H:quinine oxidoreductase (NQO1) enzymes was increased by activation of curcumin Nrf-2 [44]. Lipopolysaccharide (LPS)-stimulated BV2 mouse microglia cells also inhibited microglial activation by inhibiting the curcumin Hsp60/TLR4/MyD88/NF-κB pathways [45]. As a result, curcumin can show protective effects against cancer, neurodegeneration, and inflammation by acting on stress-response pathways.…”
Section: Curcuminmentioning
confidence: 98%